ZnO-coated PET piezoelectric electro-catalytic material easy to recover and recyclable and preparation method of ZnO-coated PET piezoelectric electro-catalytic material
By coating the ZnO ceramic mediating layer on PET fibers and growing ZnO nanorods, an easy-to-recycle ZnO@PET piezoelectric photocatalytic material is prepared, which solves the problems of difficulty in recycling existing materials and low redox efficiency, and achieves high efficiency Catalytic and excellent recycling performance.
Patent Information
- Application Number
- CN202411306165.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing piezoelectric photocatalytic materials have difficulties in recycling and recycling, resulting in limited application in industrial production and low redox efficiency of photocatalysts.
The ZnO ceramic mediator layer was coated on PET fibers by ultraviolet ozone radiation synergistic sol-gel method, and ZnO nanorods were grown by hydrothermal method to prepare easy-to-recycle and recyclable ZnO@PET piezoelectric photocatalytic material.
Improve the solid load and binding force of the catalyst, enhance carrier separation and transmission, avoid rapid recombination of electron-hole pairs, significantly improve the efficiency of catalytic degradation of organic pollutants, and realize excellent recycling of materials. sex.
Smart Images

Figure CN119186549A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric photocatalytic materials, and specifically relates to a preparation method of an easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material, and also relates to an easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material. Background Art
[0002] Photocatalysis is a process that uses light energy to drive chemical reactions. Photocatalysts are the key factor in achieving this process. They can absorb energy from sunlight or other light sources, and then convert the energy into active substances required for chemical reactions, thereby promoting the chemical reactions. Photocatalysts have broad application prospects in environmental protection, energy production, water treatment, and organic synthesis. Currently, typical photocatalysts include titanium dioxide, zinc oxide, cadmium sulfide, tungstates, and bismuth compounds. However, the electron-hole pairs excited by light in photocatalysis are particularly easy to recombine, resulting in low redox efficiency. Photocatalytic materials cannot be used on a large scale in actual industrial production.
[0003] Piezoelectric photocatalyst combines piezoelectric effect and photocatalysis, and is a new type of multifunctional photocatalytic material. It uses the piezoelectric effect to construct a built-in electric field inside the material, which can effectively promote the separation of bulk carriers while inhibiting the recombination of electron-hole pairs, thereby significantly improving the photocatalytic efficiency. ZnO, as a semiconductor with a wurtzite structure, has excellent piezoelectricity and photocatalysis. When ZnO is used as a piezoelectric photocatalyst, a piezoelectric potential is generated inside the ZnO when external pressure is applied to construct a built-in electric field. Due to the presence of polarized charges, the surface energy level of the positive polarized charge bends downward, resulting in a higher surface charge potential than before, while the surface energy level of the negative polarized charge is lower than before. This situation will facilitate the migration of electrons to the surface of the material, drive the redox reaction on the catalyst surface, and further improve the catalytic efficiency to solve the above-mentioned problem of low redox efficiency of typical photocatalysts. However, traditional ZnO catalysts are mostly powdered materials synthesized by hydrothermal methods. Directly putting the powdered catalyst into the water body will make it difficult to recover the catalyst, which is easy to cause secondary pollution of the water body. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an easily recyclable ZnO@PET piezoelectric photocatalytic material to solve the problem of difficulty in recycling existing piezoelectric photocatalytic materials.
[0005] Another object of the present invention is to provide a ZnO@PET piezoelectric photocatalytic material that is easily recyclable.
[0006] The technical solution adopted by the present invention is a method for preparing a ZnO@PET piezoelectric photocatalytic material that is easily recyclable and can be reused, which is specifically implemented according to the following steps:
[0007] Step 1, cleaning and activating the PET fiber;
[0008] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0009] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material.
[0010] The present invention is also characterized in that:
[0011] The specific process of step 1 is:
[0012] Step 1.1: Place the PET fiber in deionized water, add detergent powder and then ultrasonically clean it. Then place the cleaned PET fiber in NaCO 3 The samples were immersed in the solution, then rinsed with deionized water and dried in a drying oven;
[0013] Step 1.2, subjecting the PET fiber treated in step 1.1 to ultraviolet ozone radiation treatment.
[0014] In step 1.1, the ultrasonic cleaning time is 5 min to 20 min, the soaking time is 2 h to 6 h, the drying temperature is 30° C. to 90° C., and the drying time is 1 h to 7 h.
[0015] In step 1.2, the process parameters of the UV-ozone radiation treatment are: the wavelength of the UV light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 The radiation time is 10min to 30min.
[0016] The specific process of step 2 is:
[0017] Step 2.1, dissolving zinc acetate dihydrate in ethylene glycol methyl ether at room temperature, stirring magnetically, and after the two are evenly mixed, dropping ethanolamine into the mixed solution, and stirring magnetically in a water bath to obtain a sol, and after the sol becomes slightly yellow, transparent and clear, standing and aging to obtain a ZnO precursor sol;
[0018] Step 2.2, dipping the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration during the dipping process, then taking the PET fiber out of the ZnO precursor sol and performing centrifugal treatment, and then placing it in a drying oven for drying to obtain a PET fiber coated with a ZnO gel film;
[0019] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate, and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic intermediate layer.
[0020] In step 2.1, the molar ratio of zinc acetate dihydrate to ethanolamine is 1 to 5:1, and the concentration of the ZnO precursor sol is 0.2 mol / L to 1 mol / L;
[0021] The temperature of the water bath is 50°C to 80°C, and the static aging time is 12h to 24h.
[0022] In step 2.2, the ultrasonic vibration time is 4 min to 10 min, the centrifugal speed is 300 r / min to 1000 r / min, the centrifugal time is 3 min to 10 min, the drying temperature is 30° C. to 90° C., and the drying time is 1 h to 7 h;
[0023] In step 2.3, the temperature of the heating plate is 100℃~200℃, the wavelength of the ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 The radiation time is 0.5h~2h.
[0024] The specific process of step 3 is:
[0025] Step 3.1, dissolving zinc nitrate hexahydrate in deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving hexamethylenetetramine in deionized water, stirring and ultrasonically vibrating to completely dissolve it, and then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating it to obtain a clear ZnO nanorod hydrothermal reaction solution;
[0026] Step 3.2, placing the PET fiber with the surface uniformly coated with the ZnO ceramic mediating layer obtained in step 2 into a reactor filled with a ZnO nanorod hydrothermal reaction solution for hydrothermal reaction to obtain a PET fiber with the surface uniformly coated with ZnO nanorods;
[0027] Step 3.3, taking out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinsing it with deionized water, and drying it in a drying oven to obtain a ZnO@PET piezoelectric photocatalytic material.
[0028] In step 3.1, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1 to 2.5:1, and the Zn ion concentration of the ZnO nanorod hydrothermal reaction solution is 0.04 mol / L to 0.1 mol / L;
[0029] In step 3.2, the hydrothermal reaction temperature is 90°C to 120°C, and the hydrothermal reaction time is 9h to 15h;
[0030] In step 3.3, the drying temperature is 30° C. to 90° C., and the drying time is 1 h to 7 h.
[0031] Another technical solution adopted by the present invention is that the easily recyclable ZnO@PET piezoelectric photocatalytic material is prepared by the above-mentioned preparation method.
[0032] The beneficial effects of the present invention are:
[0033] (1) The PET fiber carrier used in the preparation method of the present invention has a fluffy porous structure, and the large specific surface area increases the solid loading amount of nano zinc oxide, which can realize the direct suspension of the catalyst material on the upper layer of the sewage, thereby facilitating full contact between sunlight, pollutants, and catalysts; in addition, the fluffy porous fiber carrier suspended on the water surface can also efficiently capture the mechanical energy generated during the movement of water surface waves, and stimulate the piezoelectric effect of ZnO, enhance carrier separation and transmission, and avoid rapid recombination of electron-hole pairs, thereby achieving excellent catalytic degradation of organic pollutants;
[0034] (2) The preparation method of the present invention first coats the ZnO seed layer on the surface of the PET fiber by a sol-gel technique combined with an ultraviolet ozone radiation modification technique, and then grows the ZnO nanorods by a hydrothermal method, thereby ensuring that the ZnO ceramic layer uniformly and densely coats each PET fiber. The ZnO nanorods are further grown hydrothermally using the ZnO ceramic layer as a mediating layer, which not only ensures a high loading rate of the ZnO nanorods, but also enables a stronger bonding force between the ZnO nanorods / ceramic layer and the PET fiber, thereby giving the ZnO@PET piezoelectric photocatalytic material excellent durability and cycle stability;
[0035] (3) The ZnO@PET piezoelectric photocatalytic material obtained by the preparation method of the present invention can be suspended on the water surface, and can be directly salvaged and reused after catalytic degradation of organic wastewater, so it is easy to recover and recycle. Under the piezoelectric-photosynergistic effect, it has a high degradation rate for organic pollutants, showing excellent catalytic performance and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is the XRD spectrum of the ZnO@PET piezoelectric photocatalytic material prepared in Example 1 of the present invention;
[0037] Figure 2 is a surface morphology photograph of the ZnO@PET piezoelectric photocatalytic material prepared in Example 2 of the present invention;
[0038] Figure 3The degradation rate of the organic pollutant MB by the ZnO@PET piezoelectric photocatalytic material prepared in Example 3 of the present invention changes with time;
[0039] Figure 4 The degradation rate constant of the organic pollutant MB by the ZnO@PET piezoelectric photocatalytic material prepared in Example 4 of the present invention changes with the number of cycles. DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material of the present invention is specifically implemented according to the following steps:
[0042] Step 1, cleaning and activating the PET fiber;
[0043] The specific process is:
[0044] Step 1.1, put PET (polyethylene terephthalate) fiber into deionized water, add detergent powder and ultrasonically clean it for 5min to 20min, then put the cleaned PET fiber into 1% NaCO 3 Soak in the solution for 2h to 6h, then rinse with deionized water and dry in a drying oven at 30℃ to 90℃ for 1h to 7h;
[0045] Step 1.2, the PET fiber treated in step 1.1 is subjected to ultraviolet ozone radiation treatment, the wavelength of the ultraviolet light used is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 , the radiation time is 10min~30min;
[0046] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0047] The specific process is:
[0048] Step 2.1, at room temperature, dissolving zinc acetate dihydrate in ethylene glycol methyl ether, magnetically stirring for 1 h to 3 h, and after the two are evenly mixed, dropping ethanolamine into the mixed solution, and magnetically stirring for 6 h to 10 h in a water bath at 50° C. to 80° C. to obtain a sol, and after the sol becomes slightly yellow, transparent and clear, standing and aging for 12 h to 24 h to obtain a ZnO precursor sol;
[0049] The molar ratio of zinc acetate dihydrate to ethanolamine is 1 to 5:1, and the concentration of ZnO precursor sol is 0.2 mol / L to 1 mol / L;
[0050] Step 2.2, impregnating the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration for 4 minutes to 10 minutes during the impregnation process, then taking the PET fiber out of the ZnO precursor sol and centrifuging it at a speed of 300r / min to 1000r / min for 3 minutes to 10 minutes, and then placing it in a drying oven at 30°C to 90°C for 1 hour to 7 hours to obtain a PET fiber coated with a ZnO gel film;
[0051] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate at 100° C. to 200° C., and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer;
[0052] The process of ultraviolet ozone radiation treatment is as follows: the wavelength of ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 , the radiation time is 0.5h~2h;
[0053] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material;
[0054] The specific process is:
[0055] Step 3.1, dissolving zinc nitrate hexahydrate in deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving hexamethylenetetramine in deionized water, stirring and ultrasonically vibrating to completely dissolve it, and then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating for 5 minutes to 15 minutes to obtain a clear ZnO nanorod hydrothermal reaction solution;
[0056] The molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1 to 2.5:1, and the Zn ion concentration of the ZnO nanorod hydrothermal reaction solution is 0.04 mol / L to 0.1 mol / L;
[0057] Step 3.2, placing the PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer obtained in step 2 into a reactor containing a ZnO nanorod hydrothermal reaction solution and performing a hydrothermal reaction at 90° C. to 120° C. for 9 h to 15 h to obtain a PET fiber with a surface uniformly coated with ZnO nanorods;
[0058] Step 3.3, take out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinse it with deionized water, put it into a drying oven at 30°C to 90°C for 1h to 7h, and obtain ZnO@PET piezoelectric photocatalytic material.
[0059] The principle of the preparation method of the present invention is that the physical and chemical properties of high molecular organic PET and inorganic ZnO nanorods are very different, and the traditional hydrothermal method cannot directly immobilize ZnO nanorods on the surface of PET fibers. In view of this problem, the present invention pre-coats a uniform and dense ZnO mediated coating on the fiber surface by ultraviolet ozone radiation and sol-gel method before the hydrothermal process, and improves the nanorod immobilization amount and density by modifying the surface of the fiber carrier. At the same time, the PET fiber carrier only plays a supporting role to prevent the powder agglomeration phenomenon from occurring and increase the overall specific surface area of the nanorod catalyst. The carrier itself does not participate in the redox reaction. ZnO is fixed on the PET fiber and can also prevent the catalyst from being lost and is easy to recover the catalyst. The lightweight PET carrier allows the catalyst to float on the water surface, which can increase the contact area between the material and the sunlight, facilitate the capture of the mechanical energy generated by the wave movement on the water surface, and directly salvage it after catalytic degradation of organic wastewater for reuse. In the process of catalytic degradation of organic wastewater, using PET lightweight fiber as a carrier can make the sample float on the upper layer of simulated pollutants, which is beneficial to the absorption of light and the stimulation of piezoelectric effect. Under the synergistic effect of piezoelectricity and light, the catalytic performance of the material is significantly improved, and the organic pollutant methylene blue (MB) in the wastewater can be effectively degraded, thus showing excellent recycling performance.
[0060] Example 1
[0061] Step 1, cleaning and activating the PET fiber;
[0062] The specific process is:
[0063] Step 1.1, put the PET fiber into deionized water, add detergent powder and ultrasonically clean it for 5 minutes, then put the cleaned PET fiber into a 1% NaCO 3 Soak in the solution for 2 h, then rinse with deionized water and dry in a drying oven at 30 °C for 7 h;
[0064] Step 1.2, the PET fiber treated in step 1.1 is subjected to ultraviolet ozone radiation treatment, the main wavelength of the ultraviolet light used is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 , the radiation time is 10min;
[0065] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0066] The specific process is:
[0067] Step 2.1, at room temperature, dissolve 4.39 g of zinc acetate dihydrate in 100 ml of ethylene glycol methyl ether, and stir magnetically for 1 h. After the two are evenly mixed, drop 1.22 g of ethanolamine into the mixed solution, and stir magnetically for 6 h in a water bath at 50° C. to obtain a sol. After the sol becomes slightly yellow, transparent and clear, stand and age for 12 h to obtain a ZnO precursor sol with a concentration of 0.2 mol / L.
[0068] Wherein, the molar ratio of zinc acetate dihydrate to ethanolamine is 1:1;
[0069] Step 2.2, impregnating the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration for 4 minutes during the impregnation process, then taking the PET fiber out of the ZnO precursor sol and centrifuging it at a speed of 300r / min for 3 minutes, and then placing it in a drying oven at 30°C for 7 hours to obtain a PET fiber coated with a ZnO gel film;
[0070] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate at 100° C., and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer;
[0071] The process of ultraviolet ozone radiation treatment is as follows: the wavelength of ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 , the radiation time is 0.5h;
[0072] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material;
[0073] The specific process is:
[0074] Step 3.1, dissolving 0.596 g zinc nitrate hexahydrate in 25 ml deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving 0.280 g hexamethylenetetramine in 25 ml deionized water, stirring and ultrasonically vibrating to completely dissolve it, then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating for 5 minutes to obtain a clear ZnO nanorod hydrothermal reaction solution with a concentration of 0.04 mol / L;
[0075] Wherein, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1:1;
[0076] Step 3.2, placing the PET fiber with the surface uniformly coated with the ZnO ceramic mediating layer obtained in step 2 into a reactor filled with a ZnO nanorod hydrothermal reaction solution and performing a hydrothermal reaction at 90° C. for 9 hours to obtain a PET fiber with the surface uniformly coated with ZnO nanorods;
[0077] Step 3.3, take out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinse it with deionized water, put it into a drying oven at 30° C. and dry it for 7 hours to obtain ZnO@PET piezoelectric photocatalytic material.
[0078] The XRD spectrum of the ZnO@PET piezoelectric photocatalytic material prepared in this example is shown in Figure 1 As shown, it can be clearly observed that the crystal plane derivative peaks at 18°, 23°, and 27° in the spectrum still belong to the PET fiber carrier. In addition, we also observed obvious diffraction peaks belonging to the ZnO nanorods, and the positions and intensities of the relevant peaks are consistent with the crystal planes (100), (002), (101), (102), (110), (103), (112), and (004) in the ZnO wurtzite structure standard PDF card (card number: #89-1397), proving that the ZnO nanorods immobilized on the surface of the PET fiber in the experiment are all pure phase hexagonal wurtzite structure. We also did not find other derivative peaks in the XRD spectrum, indicating that the sample does not contain other intermediates or impurities.
[0079] The ZnO@PET piezoelectric photocatalytic material prepared in this embodiment degrades the MB solution under the synergistic effect of xenon lamp irradiation + ultrasonic vibration. The measurement shows that the MB degradation amount has reached 40.5% after 25 minutes, 52.7% after 50 minutes, 60.3% after 75 minutes, 75.2% after 100 minutes, and 82.8% after 125 minutes. The degradation rate constant is 0.0165min -1 After the first catalytic degradation, the catalyst was removed and added to the second MB solution of the same concentration. The degradation rate constant of the catalyst to MB was tested under the same conditions. When the degradation cycle number reached 25 times, the degradation rate constant was 0.0165min -1 , the degradation rate constant at 50 times is 0.0162min -1 , the degradation rate constant at 75 times is 0.0161min -1 , the degradation rate constant at 100 times is 0.0159min -1 ; With the increase of cycle number, the degradation rate constant does not decrease significantly, which proves that the material has excellent recycling performance.
[0080] Example 2
[0081] Step 1, cleaning and activating the PET fiber;
[0082] The specific process is:
[0083] Step 1.1: Place the PET fiber in deionized water, add detergent powder and ultrasonically clean it for 10 minutes, then place the cleaned PET fiber in a 1% NaCO 3 Soak in the solution for 3 h, then rinse with deionized water and dry in a drying oven at 50 °C for 5 h;
[0084] Step 1.2, the PET fiber treated in step 1.1 is subjected to ultraviolet ozone radiation treatment, the wavelength of the ultraviolet light used is a combination of 185nm and 254nm, and the radiation intensity is 3750W / m 2 , the radiation time is 15min;
[0085] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0086] The specific process is:
[0087] Step 2.1, at room temperature, dissolve 8.78g of zinc acetate dihydrate in 100ml of ethylene glycol methyl ether, and stir magnetically for 1h. After the two are evenly mixed, 1.22g of ethanolamine is dropped into the mixed solution, and magnetic stirring is performed for 7h in a water bath at 60°C to obtain a sol. After the sol becomes slightly yellow, transparent and clear, it is allowed to stand for 16h to obtain a ZnO precursor sol with a concentration of 0.4mol / L.
[0088] Wherein, the molar ratio of zinc acetate dihydrate to ethanolamine is 2:1;
[0089] Step 2.2, impregnating the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration for 5 minutes during the impregnation process, then taking the PET fiber out of the ZnO precursor sol and centrifuging it at a speed of 500r / min for 5 minutes, and then placing it in a drying oven at 50°C for 5 hours to obtain a PET fiber coated with a ZnO gel film;
[0090] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate at 130° C., and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer;
[0091] The process of ultraviolet ozone radiation treatment is as follows: the wavelength of ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 3750W / m 2 , the radiation time is 1h;
[0092] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material;
[0093] The specific process is:
[0094] Step 3.1, dissolving 0.893 g zinc nitrate hexahydrate in 25 ml deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving 0.280 g hexamethylenetetramine in 25 ml deionized water, stirring and ultrasonically vibrating to completely dissolve it, then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating for 10 minutes to obtain a clear ZnO nanorod hydrothermal reaction solution with a concentration of 0.06 mol / L;
[0095] Wherein, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1.5:1;
[0096] Step 3.2, placing the PET fiber with the surface uniformly coated with the ZnO ceramic mediating layer obtained in step 2 into a reactor filled with a ZnO nanorod hydrothermal reaction solution and performing a hydrothermal reaction at 120° C. for 12 hours to obtain a PET fiber with the surface uniformly coated with ZnO nanorods;
[0097] Step 3.3, take out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinse it with deionized water, put it into a drying oven at 50° C. and dry it for 5 hours to obtain ZnO@PET piezoelectric photocatalytic material.
[0098] In this example, SEM was used to analyze the immobilization of ZnO@PET piezoelectric photocatalytic material. Figure 2 The SEM photos shown show that under hydrothermal conditions at 120°C, the ZnO nanorods completely and densely cover the surface of the PET fibers, and the arrangement structure is dense and uniform. Figure 2 All nanostructures showed obvious hexagonal rod-like structures and there was no adhesion between the rods. The ZnO coating on the surface of the PET fiber did not have cracks, which indicates that the mediating layer played a certain protective role on the PET fiber during the hydrothermal process.
[0099] The ZnO@PET piezoelectric photocatalytic material prepared in this embodiment degrades the MB solution under the synergistic effect of xenon lamp irradiation + ultrasonic vibration. The measurement shows that the MB degradation amount reaches 42.5% after 25 minutes, 53.4% after 50 minutes, 63.5% after 75 minutes, 82.6% after 100 minutes, and 89.4% after 125 minutes. The degradation rate constant is 0.0176min -1After one catalytic degradation, the catalyst was removed and added to the second MB solution of the same concentration. The degradation rate constant of the catalyst on MB was tested under the same conditions. When the number of degradation cycles reached 25, the degradation rate constant was 0.0176min -1 , the degradation rate constant at 50 times is 0.0172min -1 , the degradation rate constant at 75 times is 0.0171min -1 , the degradation rate constant at 100 times is 0.0169min -1 ; With the increase of cycle number, the degradation rate constant does not decrease significantly, which proves that the material has excellent recycling performance.
[0100] Example 3
[0101] Step 1, cleaning and activating the PET fiber;
[0102] The specific process is:
[0103] Step 1.1, put the PET fiber into deionized water, add detergent powder and ultrasonically clean it for 15 minutes, then put the cleaned PET fiber into a 1% NaCO 3 Soak in the solution for 4 h, then rinse with deionized water and dry in a drying oven at 80 °C for 3 h;
[0104] Step 1.2, the PET fiber treated in step 1.1 is subjected to ultraviolet ozone radiation treatment, the wavelength of the ultraviolet light used is a combination of 185nm and 254nm, and the radiation intensity is 5000W / m 2 , the radiation time is 20min;
[0105] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0106] The specific process is:
[0107] Step 2.1, at room temperature, dissolve 17.56 g of zinc acetate dihydrate in 100 ml of ethylene glycol methyl ether, and stir magnetically for 1 hour. After the two are evenly mixed, drop 1.22 g of ethanolamine into the mixed solution, and stir magnetically for 8 hours in a water bath at 70° C. to obtain a sol. After the sol becomes slightly yellow, transparent and clear, stand and age for 20 hours to obtain a ZnO precursor sol with a concentration of 0.8 mol / L.
[0108] Wherein, the molar ratio of zinc acetate dihydrate to ethanolamine is 4:1;
[0109] Step 2.2, impregnating the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration for 7 minutes during the impregnation process, then taking the PET fiber out of the ZnO precursor sol and centrifuging it at a speed of 700r / min for 7 minutes, and then drying it in a drying oven at 80°C for 3 hours to obtain a PET fiber coated with a ZnO gel film;
[0110] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate at 160° C., and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer;
[0111] The process of ultraviolet ozone radiation treatment is as follows: the wavelength of ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 5000W / m 2 , the radiation time is 1.5h;
[0112] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material;
[0113] The specific process is:
[0114] Step 3.1, dissolving 1.19 g of zinc nitrate hexahydrate in 25 ml of deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving 0.280 g of hexamethylenetetramine in 25 ml of deionized water, stirring and ultrasonically vibrating to completely dissolve it, then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating for 15 minutes to obtain a clear ZnO nanorod hydrothermal reaction solution with a concentration of 0.08 mol / L;
[0115] Wherein, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2:1;
[0116] Step 3.2, placing the PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer obtained in step 2 into a reactor containing a ZnO nanorod hydrothermal reaction solution and performing a hydrothermal reaction at 100° C. for 13 hours to obtain a PET fiber with a surface uniformly coated with ZnO nanorods;
[0117] Step 3.3, take out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinse it with deionized water to remove the ZnO powder with poor bonding force attached to the surface, put it into a drying oven at 80°C for 3 hours, and obtain ZnO@PET piezoelectric photocatalytic material.
[0118] Figure 3The following is a comparison chart of the degradation trend under three catalytic conditions: ultrasonic oscillation, xenon lamp irradiation, and xenon lamp irradiation + ultrasonic oscillation in the dark. Compared with simple ultrasonic oscillation, the absorbance of the solution decreases faster under xenon lamp irradiation. It is calculated that the MB degradation after 25, 50, 75, 100, and 125 minutes of illumination is 19.2%, 32.2%, 48.0%, 64.4%, and 72.1%, respectively; under the synergistic effect of xenon lamp irradiation + ultrasonic oscillation, the absorbance decrease rate of MB solution is more obvious. It is calculated that the MB degradation has reached 43.1% after 25 minutes, 54.1% after 50 minutes, 65.1% after 75 minutes, 83.5% after 100 minutes, and 92.7% after 125 minutes; the figure directly reflects that the sample has the best catalytic effect on MB under the synergistic effect of xenon lamp irradiation + ultrasonic oscillation, second only to light conditions, and the worst only under oscillation conditions. Under the synergistic effect of ultrasonic vibration and light, the degradation rate constant of the catalyst for the organic pollutant MB is 0.0184min -1 , and the photodegradation rate constant under visible light conditions is 0.0098min -1 It can be seen that the photodegradation rate constant of organic pollutants by the ZnO@PET catalytic material prepared by the present invention under ultrasonic oscillation-light synergy is about twice that under visible light conditions, proving that the built-in electric field constructed by the piezoelectric effect of nanorods significantly improves the degradation efficiency of organic pollutants in sewage by the ZnO@PET piezoelectric photocatalytic material.
[0119] After one catalytic degradation was completed, the catalyst was removed and added to the second MB solution of the same concentration. The degradation rate constant of the catalyst on MB was tested under the synergistic effect of ultrasonic vibration and light. When the number of degradation cycles reached 25, the degradation rate constant was 0.0184min -1 , the degradation rate constant at 50 times is 0.0182min -1 , the degradation rate constant at 75 times is 0.0179min -1 , the degradation rate constant at 100 times is 0.0178min -1 ; With the increase of cycle number, the degradation rate constant does not decrease significantly, which proves that the material has excellent recycling performance.
[0120] Example 4
[0121] Step 1, cleaning and activating the PET fiber;
[0122] The specific process is:
[0123] Step 1.1: Place the PET fiber in deionized water, add detergent powder and ultrasonically clean it for 20 minutes, then place the cleaned PET fiber in a 1% NaCO 3Soak in the solution for 6 h, then rinse with deionized water and dry in a drying oven at 90 °C for 1 h;
[0124] Step 1.2, the PET fiber treated in step 1.1 is subjected to ultraviolet ozone radiation treatment, the wavelength of the ultraviolet light used is a combination of 185nm and 254nm, and the radiation intensity is 6250W / m 2 , the radiation time is 30min;
[0125] Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method;
[0126] The specific process is:
[0127] Step 2.1, at room temperature, dissolve 21.95 g of zinc acetate dihydrate in 100 ml of ethylene glycol methyl ether, and stir magnetically for 1 h. After the two are evenly mixed, drop 1.22 g of ethanolamine into the mixed solution, and stir magnetically for 10 h in a water bath at 80° C. to obtain a sol. After the sol becomes slightly yellow, transparent and clear, stand and age for 24 h to obtain a ZnO precursor sol with a concentration of 1 mol / L.
[0128] Wherein, the molar ratio of zinc acetate dihydrate to ethanolamine is 5:1;
[0129] Step 2.2, impregnating the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration for 10 minutes during the impregnation process, then taking the PET fiber out of the ZnO precursor sol and centrifuging it at a speed of 1000r / min for 10 minutes, and then placing it in a drying oven at 90°C for 1 hour to obtain a PET fiber coated with a ZnO gel film;
[0130] Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate at 200° C., and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic mediating layer;
[0131] The process of ultraviolet ozone radiation treatment is as follows: the wavelength of ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 6250W / m 2 , the radiation time is 2h;
[0132] Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material;
[0133] The specific process is:
[0134] Step 3.1, dissolving 1.488 g of zinc nitrate hexahydrate in 25 ml of deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving 0.280 g of hexamethylenetetramine in 25 ml of deionized water, stirring and ultrasonically vibrating to completely dissolve it, then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating for 15 minutes to obtain a clear ZnO nanorod hydrothermal reaction solution with a concentration of 0.1 mol / L;
[0135] Wherein, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 2.5:1;
[0136] Step 3.2, placing the PET fiber with the surface uniformly coated with the ZnO ceramic mediating layer obtained in step 2 into a reactor filled with a ZnO nanorod hydrothermal reaction solution and performing a hydrothermal reaction at 120° C. for 15 hours to obtain a PET fiber with the surface uniformly coated with ZnO nanorods;
[0137] Step 3.3, take out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinse it with deionized water, put it into a drying oven at 90° C. for 1 hour, and obtain the ZnO@PET piezoelectric photocatalytic material.
[0138] The ZnO@PET piezoelectric photocatalytic material prepared in this embodiment degrades the MB solution under the synergistic effect of xenon lamp irradiation + ultrasonic vibration. The measurement shows that the MB degradation amount has reached 44.7% after 25 minutes, 56.4% after 50 minutes, 67.8% after 75 minutes, 85.6% after 100 minutes, and 93.4% after 125 minutes. The degradation rate constant is 0.0196 min -1 After the first catalytic degradation is completed, the catalyst is removed and added to the second MB solution of the same concentration, and the degradation rate constant of the catalyst on MB is tested under the same conditions. Figure 4 As shown in Figure 2, when the degradation cycle number reaches 25, the degradation rate constant is 0.0196min -1 , the degradation rate constant at 50 times is 0.0194min -1 , the degradation rate constant at 75 times is 0.0191min -1 , the degradation rate constant at 100 times is 0.0189min -1 ; With the increase of cycle number, the degradation rate constant does not decrease significantly, which proves that the material has excellent recycling performance.
Claims
1. A method for preparing an easily recyclable ZnO@PET piezoelectric photocatalytic material, characterized in that: Follow the steps below to implement it: Step 1, cleaning and activating the PET fiber; Step 2, preparing PET fibers with a surface uniformly coated with a ZnO ceramic mediating layer by using ultraviolet ozone radiation in conjunction with a sol-gel method; Step 3, using a hydrothermal method to continue growing ZnO nanorods on the PET fiber with the ZnO ceramic mediating layer uniformly coated on the surface, to obtain a ZnO@PET piezoelectric photocatalytic material.
2. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 1, characterized in that: The specific process of step 1 is: Step 1.1, placing the PET fiber in deionized water, adding detergent powder and then ultrasonically cleaning, then soaking the cleaned PET fiber in a NaCO3 solution, then rinsing with deionized water, and drying in a drying oven; Step 1.2, subjecting the PET fiber treated in step 1.1 to ultraviolet ozone radiation treatment.
3. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 2, characterized in that: In step 1.1, the ultrasonic cleaning time is 5 min to 20 min, the soaking time is 2 h to 6 h, the drying temperature is 30° C. to 90° C., and the drying time is 1 h to 7 h.
4. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 2, characterized in that: In step 1.2, the process parameters of the UV-ozone radiation treatment are: the wavelength of the UV light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 The radiation time is 10min to 30min.
5. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 1, characterized in that: The specific process of step 2 is: Step 2.1, dissolving zinc acetate dihydrate in ethylene glycol methyl ether at room temperature, stirring magnetically, and after the two are evenly mixed, dropping ethanolamine into the mixed solution, and stirring magnetically in a water bath to obtain a sol, and after the sol becomes slightly yellow, transparent and clear, standing and aging to obtain a ZnO precursor sol; Step 2.2, dipping the PET fiber treated in step 1 into the ZnO precursor sol obtained in step 2.1, performing ultrasonic vibration during the dipping process, then taking the PET fiber out of the ZnO precursor sol and performing centrifugal treatment, and then placing it in a drying oven for drying to obtain a PET fiber coated with a ZnO gel film; Step 2.3, placing the PET fiber coated with the ZnO gel film obtained in step 2.2 on a heating plate, and simultaneously subjecting the PET fiber coated with the ZnO gel film to ultraviolet ozone radiation treatment during the heating process to obtain a PET fiber with a surface uniformly coated with a ZnO ceramic intermediate layer.
6. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 5, characterized in that: In step 2.1, the molar ratio of zinc acetate dihydrate to ethanolamine is 1 to 5:1, the concentration of ZnO precursor sol is 0.2 mol / L to 1 mol / L; the temperature of the water bath is 50° C. to 80° C., and the standing aging time is 12 h to 24 h; In step 2.2, the ultrasonic vibration time is 4 min to 10 min, the centrifugal speed is 300 r / min to 1000 r / min, the centrifugal time is 3 min to 10 min, the drying temperature is 30° C. to 90° C., and the drying time is 1 h to 7 h.
7. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 5, characterized in that: In step 2.3, the temperature of the heating plate is 100℃~200℃, the wavelength of the ultraviolet light is a combination of 185nm and 254nm, and the radiation intensity is 2500W / m 2 ~6250W / m 2 The radiation time is 0.5h~2h.
8. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 1, characterized in that: The specific process of step 3 is: Step 3.1, dissolving zinc nitrate hexahydrate in deionized water, stirring and ultrasonically vibrating to completely dissolve it, dissolving hexamethylenetetramine in deionized water, stirring and ultrasonically vibrating to completely dissolve it, and then pouring the hexamethylenetetramine solution into the zinc nitrate hexahydrate solution and ultrasonically vibrating it to obtain a clear ZnO nanorod hydrothermal reaction solution; Step 3.2, placing the PET fiber with the surface uniformly coated with the ZnO ceramic mediating layer obtained in step 2 into a reactor filled with a ZnO nanorod hydrothermal reaction solution for hydrothermal reaction to obtain a PET fiber with the surface uniformly coated with ZnO nanorods; Step 3.3, taking out the PET fiber with the surface uniformly coated with ZnO nanorods obtained in step 3.2, rinsing it with deionized water, and drying it in a drying oven to obtain a ZnO@PET piezoelectric photocatalytic material.
9. The method for preparing the easily recyclable and reusable ZnO@PET piezoelectric photocatalytic material according to claim 8, characterized in that: In step 3.1, the molar ratio of zinc nitrate hexahydrate to hexamethylenetetramine is 1 to 2.5:1, and the Zn ion concentration of the ZnO nanorod hydrothermal reaction solution is 0.04 mol / L to 0.1 mol / L; in step 3.2, the hydrothermal reaction temperature is 90°C to 120°C, and the hydrothermal reaction time is 9h to 15h; in step 3.3, the drying temperature is 30°C to 90°C, and the drying time is 1h to 7h.
10. The ZnO@PET piezoelectric photocatalytic material is easy to recycle and can be reused, characterized in that: The preparation method is described in any one of claims 1 to 9.
